Entrepreneurial intention and job preferences of business students of Chile - Araya-Pizarro, Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of the study is to analyze the labor preferences and Entrepreneurial Intention (EI) of business students in Chile, through the application of a discrete choice model, based on four characteristic entrepreneurial traits: autonomy, innovation, power and altruism. The findings, derived from a survey applied to 85 university students, reveal that the student body prefers to be the owner of a lucrative, innovative and high-income company. It was revealed that in the labor predilections of students with high EI, the trinomial autonomy, power and innovation prevails, while in students with low EI the binomial power and autonomy prevails. Altruism, for its part, was the least relevant decisional attribute. It is concluded that labor preferences are linked to the EI level of the students. Traits such as: autonomy, power and innovative vocation, constitute factors underlying the occupational propensity. This information is relevant for university courses that teach entrepreneurship and that wish to design effective programmatic offers that consider the work preferences of students.